Brusatol Regulates Ferroptosis of Ovarian Cancer Through the Nrf2/HO-1/NQO1 and AKT/mTOR Double Signaling Pathways - Liu, Hongli; Wang, Luyao; Hu, Mengling; Hua, Jiale; Lian, Xiaofu; Lian, Chaoqun; Zhang, Jing (Current Pharmaceutical Design, 2025)
<span class=
Keywords: Nrf2/HO-1/NQO1 pathway